2017
DOI: 10.1371/journal.pone.0189837
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific reference intervals of hematologic and biochemical analytes in Sprague-Dawley rats using the nonparametric rank percentile method

Abstract: BackgroundHematologic and biochemical analytes of Sprague-Dawley rats are commonly used to determine effects that were induced by treatment and to evaluate organ dysfunction in toxicological safety assessments, but reference intervals have not been well established for these analytes. Reference intervals as presently defined for these analytes in Sprague-Dawley rats have not used internationally recommended statistical method nor stratified by sex. Thus, we aimed to establish sex-specific reference intervals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
60
2
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 56 publications
19
60
2
13
Order By: Relevance
“…Despite the fluctuating food and water intake, the body weight measurements showed elevating trends, indicating normal development of the TS. Similar body weight trends were also reported by other authors [ 30 , 31 , 32 ]. Hence, it is concluded that the fluctuations observed in the food and water intake did not cause any treatment-related effects in the TS.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fluctuating food and water intake, the body weight measurements showed elevating trends, indicating normal development of the TS. Similar body weight trends were also reported by other authors [ 30 , 31 , 32 ]. Hence, it is concluded that the fluctuations observed in the food and water intake did not cause any treatment-related effects in the TS.…”
Section: Discussionsupporting
confidence: 91%
“…The hepatotoxicity was induced in animals by CCl 4 injections and led to an increase in serum aminotransferase AST and ALT levels, generally being an AST > ALT relationship in the toxic situations [ 71 ], wherein both the AST and ALT were considered as biomarkers of liver damage [ 72 , 73 , 74 , 75 ]. In the current study, rats with CCl 4 -induced hepatotoxicity were confirmed to have significantly increased levels of AST and ALT in the negative control compared to the intact group of animals ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…41,42 To our knowledge, this is the first report of thrombocytopenia as a phenotype of experimental PAH. Considering the normal lab value range for rats is higher than that of humans, 43 and hemoconcentration due to dehydration may be a confounding effect, the severity of thrombocytopenia in our study is profound. This model may help reveal mechanisms involved in development of thrombocytopenia in selected PAH patient populations.…”
Section: Discussionmentioning
confidence: 82%